Contracts, Constraints and Consumption - Green, Edward J.; Oh, Soo-Nam (Review of Economic Studies, 1991)
The paper compares implications of three kinds of models of households' consumption behaviour: the basic permanent-income model, several models of liquidity-constrained households, and a model of an informationally-constrained efficient contract. These models are distinguished in terms of implications regarding the present discounted values of net trades to households at various levels of temporary income, and the households' marginal rates of substitution. Martingale consumption is studied as an approximation to the predicted consumption process of the efficient-contract model.